2017
DOI: 10.1016/j.simyco.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic taxonomy of Aspergillus section Aspergillus (formerly Eurotium), and its occurrence in indoor environments and food

Abstract: Aspergillus section Aspergillus (formerly the genus Eurotium) includes xerophilic species with uniseriate conidiophores, globose to subglobose vesicles, green conidia and yellow, thin walled eurotium-like ascomata with hyaline, lenticular ascospores. In the present study, a polyphasic approach using morphological characters, extrolites, physiological characters and phylogeny was applied to investigate the taxonomy of this section. Over 500 strains from various culture collections and new isolates obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 180 publications
6
80
0
1
Order By: Relevance
“…This was consistent with an observation that A. chevarieri produces yellow ascomata and en masse grayish-green conidia (Chen et al, 2017).…”
Section: A Chevalieri a Montevidensis And A Sydowii Were Previousupporting
confidence: 93%
See 3 more Smart Citations
“…This was consistent with an observation that A. chevarieri produces yellow ascomata and en masse grayish-green conidia (Chen et al, 2017).…”
Section: A Chevalieri a Montevidensis And A Sydowii Were Previousupporting
confidence: 93%
“…The benA, caM, and rpb2 genes, which encode β-tubulin, calmodulin, and the second largest subunit of RNA polymerase II, respectively, were then sequenced to further identify strains M1, M2, M3, and M4. The benA, caM, and rpb2 genes have been used for species-level identification of Aspergillus (Samson et al, 2014;Chen et al, 2017). Colony PCR analysis was performed using the following primer sets: Bt 2 a and Bt 2 b for benA (Glass and Donaldson, 1995); CMD5 and CMD6 for caM (Hong et al, 2005); 5F and 7CR for rpb2 (Liu et al, 1999).…”
Section: Factory-dependent Fungal Population)mentioning
confidence: 99%
See 2 more Smart Citations
“…Aspergillus pseudoglaucus (Chen et al 2017), identified in 1929, is a xerophilic filamentous fungus belonging to Aspergillus section Aspergillus. It has been isolated from seafoods and soil (Smetanina et al 2007;S eguin et al 2014).…”
Section: Aspergillus Pseudoglaucus; Mitochondrial Genome; a Xerophilimentioning
confidence: 99%